Novel diversity of Anaerolineae and Tepidiformia recovered from metagenomes of thermal microbial mats in Costa Rica - Brenes Guillén, Laura Natalia (2025)
Tropical thermal and mineral springs are ideal for studying microbial life in extreme environments, their microbial diversity and functional profiles. In this work, we investigated the abundance and genomic diversity of the phylum Chloroflexota in microbial mats from 33 thermal and acidic springs across Costa Rica using 16S rRNA gene amplicon sequencing and shotgun metagenomics. Our results demonstrate that pH and temperature are the main environmental drivers shaping Chloroflexota abundance and diversity. Acidic conditions favored the presence of Ktedonobacteria and candidate division AD3, while thermal environments were dominated by unclassified Anaerolineae. From a subset of thermal springs, we reconstructed 72 metagenome assembled genomes (MAGs), many representing previously uncharacterized lineages. Comparative genomic analyses revealed two novel families and new seven genus within Anaerolineae and a distinct lineage within Tepidiformia. We propose the name Ca.Sittenfelaceae, Ca. Mariellaceae and Ca.Tepidiforma platanarica. Functional annotation of Anaerolineae and Tepidiformia MAGs suggests functional redundancy. Genes for methanogenesis, dissimilatory nitrate reduction, sulfur metabolism, and methylotrophy were detected, while genes for photosynthesis, nitrogen fixation, and nitrification were absent. Unique gene clusters were identified in each family, and interestingly, 23% of these unique genes were of unknown function, highlighting the unexplored genetic potential of these organisms. Canonical correspondence analysis further showed that temperature significantly influences Anaerolineae microdiversity. This study provides the first genomic dataset of Chloroflexota from Central American geothermal environments and highlights tropical geothermal springs as reservoirs of novel microbial diversity and functional potential.